POLA PEMBIAYAAN USAHA PERIKANAN RAKYAT OLEH PT. PUPUK KALTIM DI WILAYAH PESISIR KOTA BONTANG - Muhammad Syafril (2339-1324, 2014)
The objectives of this study were: (1) to identify lending patterns of the traditional fisheries business conducted by PT Pupuk Kaltim in coastal Bontang; (2) to determine the credit mechanism distribution. This study carried out between June and November 2012 and the studied area was in coastal Bontang. The results showed that: (1) Lending patterns of fisheries artisanal business from PT. Pupuk kaltim was developed through Partnerships Community Development Program (PKBL). In performing its functions and duties, PKBL was assisted by Fisheries and Marine Farmers Association (HPPK); (2) Partnerships Community Development Program (PKBL) has two lending patterns of the fisheries business, namely: (a) financial schemes to bankable fishery business. Loans were given to the group members ranging from IDR 1,000,000,- up to IDR 10,000,000,-; (b) financial schemes to fisheries collectors with the loan limit is IDR 50,000,000.-; and 3) the credit mechanism has nine steps starting from proposal submission delivered by the candidate up to the partners involvement in the intended activities held by PKBL.